Вплив тринексапак-етилу на накопичення ортофосфатів рослинами озимої пшениці (Triticum aestivum L.) - Вірич, П.А.; Маковейчук, Т.І.; Каменчук, О.П. (Фактори експериментальної еволюції організмів, 2013)
Aims. Phosphate is one from necessary nutritious elements for plants. We studied the influence of trinexapac-ethyl (TE) (Moddus 250 к.e) on the accumulation of phosphate ions in seeding of winter wheat varieties Smuglanka. Methods. 3-dey seedlings of winter wheat treated orthophosphate and trinexapac-ethyl solutions. Samples treated only phosphate was control. Results. TE increases the quantity of orthophosphate in the stem on 45 % that is the effect of TE on the absorption and transport activity of phosphorus in wheat plants, thus contributing to the accumulation of free forms in the ground part of the plant. Conclusions. The data indicate that TE influence the absorption and transport activity of phosphorus in plants of winter wheat.